"That's My Number One Fear in Life. It's the Police": Examining Young Black Men's Exposures to Trauma and Loss Resulting From Police Violence and Police Killings. (April 2019) - Smith Lee, Jocelyn R.; Robinson, Michael A.
Black males are disproportionately the victims of police killings in the United States, yet few studies have examined their personal narratives of trauma and bereavement resulting from police violence. Informed by critical race theory and stress and coping theory, we used a modified grounded theory approach to conduct and analyze in-depth, semistructured life history interviews with 40 young Black men (aged 18-24 years) in Baltimore, Maryland. Study participants were recruited from a GED and job readiness center serving Baltimore youth. Study results offer a nuanced understanding of the patterning and mental health consequences of police violence for young Black men. Participant disclosures of witnessing and experiencing police violence began in childhood and spanned through emerging adulthood, met Diagnostic and Statistical Manual of Mental Disorders–Fifth Edition criteria for trauma exposure, and embodied theoretical conceptualizations of racial trauma. Exposures to police violence fostered distrust of police and informed participants' appraisals of their vulnerability to police violence across the life course. Six study participants disclosed losing loved ones to police killings. Injustice and hypervigilance accompanied grief. Implications for research, policy, and practice are discussed.